Tension Force Stress Downregulates the Expression of Osteogenic Markers and Mineralization in Embryonic Stem-Cell-Derived Embryoid Bodies - Ju-Hyeon An; Chun-Choo Kim; Junil Lee; Junhyeok Kim; Jeong-Chae Lee; Sung-Ho Kook (Cells)
Mechanical stresses affect a variety of cellular events in relation to the frequency, magnitude, and duration of the stimuli applied. Embryonic stem cell (ESC)-derived embryoid bodies (EBs) are pluripotent stem cell aggregates and comprise all somatic cells. Numerous studies have highlighted the effects of mechanosignals on stem cells, whereas their impact on EBs has been barely investigated. Here, we examined how cyclic tensile stress affects the behavior of EBs to differentiate into mineralized osteocytes by applying 2% elongation at 0.5 Hz frequency for 1 h once or 1 h every other day for 5 or 14 days in osteogenic medium. EBs that expressed undifferentiated markers, Oct4 and Sox2, were differentiated into mineralized cells, along with the accumulation of runt-related transcription factor 2 (RUNX2) and β-catenin in osteogenic medium. The application of tensile force inhibited EB’ mineralization via the downregulation of bone sialoprotein, osteocalcin, osterix, and RUNX2. While the transfection with si-β-catenin did not affect the osteogenic potency of EBs at a significant level, treatment with 10 μM of PD98059, but not of SP600125 or SB203580, diminished the mineralization of EBs and the expression of RUNX2 and RUNX2-regulated osteoblastic genes. The level of phosphorylated extracellular signal-regulated kinase-1 (p-ERK1) rather than p-ERK2 was more apparently diminished in tension-applied EBs. The transfection with si-ERK1, but not with si-ERK2, suppressed the mineralization of osteogenic medium-supplied EBs and the expression of osteoblast-specific genes. Collectively, this study demonstrates that tensile stress inhibits osteogenic potency of EBs by downregulating ERK1-mediated signaling and osteogenic gene expression.